Do the population density and coverage rate of transit affect the public transport contribution?. Issue 1 (31st December 2022) - Jasim, Ihsan Abbas; Al-Jaberi, Ahmed Abdulsalam; Al-Maliki, Laheab A.; Al-Ansari, Nadhir; Al-Mamoori, Sohaib K.
Abstract: The article tried to study the public transport role as one of the means that contribute to sustainable urban development by investigating the effect of the coverage rate for public transport on the number of those who use public transport in the neighbourhoods of Kut city. This article investigates the link between public transportation and supportive urban design trends. The research spatial and temporal limits are represented by the municipal boundaries Al-Kut city, which are shown in the master plan of the city for the period 2008–2012. The results showed a positive but weak relationship between public transport (variable factor) and the proportion of public transport coverage and population density (independent factors). These factors do not explain the apparent, which is confirmed by the high Bo value and its great reliability, and this result is inconsistent with the hypothesis that states a positive effect between public transport and the coverage rate. However, this relationship is abnormal and indicates an imbalance in the distribution of land uses and the provision of services in the structure of Kut city. Furthermore, it is a negative indicator of the city's structure, where a good and efficient structure requires a strong relationship. As for public transport passengers, they seem to be restricted by this for poor services.